Motivational drivers and Sense of Belonging: unpacking the persistence in Chinese Martial Arts practice among international practitioners - Cao, Xueying; Lyu, Hui (Frontiers in Psychology, 2024)
Background Chinese Martial Arts (CMAs) have garnered a global following, with their rich historical and cultural heritage transcending geographical and cultural differences, sparking profound interest among an international community. As an increasing number of non-Chinese individuals persist in practicing CMAs, investigating the motivations behind their continued participation has emerged as a compelling question. This study aims to delve deeper into the factors driving international practitioners to sustain their practice of CMAs, thereby broadening our understanding of the global resonance of CMAs. Methods Employing Self-Determination Theory, 226 international CMAs practitioners completed the Physical Activity and Leisure Motivation Scale, Perceived Belonging Scale, and Persistence in Practicing CMAs Scale. SPSS 20.0 was utilized for conducting descriptive statistics, common method bias tests, and correlation analyses. Structural equation modeling was performed using AMOS 26.0. Results Motivation for Practicing CMAs, comprised of enjoyment, mastery, physical condition, psychological condition, and appearance, has a positive impact on Persistence in Practicing CMAs (β = 0.297, p < 0.01). Sense of Belonging also positively affects Persistence in Practicing CMAs (β = 0.268, p < 0.01). The aforementioned variables account for 22.1% of the variance in Persistence in Practicing CMAs. Furthermore, Affiliation, Competition/Ego, and Others’ Expectations were found to have no significant correlation with Persistence in Practicing CMAs. Conclusion The formation of persistence in the practice of CMAs among international practitioners is propelled by their ongoing desire for skill mastery, enjoyment, enhanced physical and mental health, body shape improvement, and a Sense of Belonging. The study reveals that a stronger motivation and Sense of Belonging significantly enhance their commitment to CMAs. Recommendations include that international instructors should center their teaching strategies around the practitioners, helping them to find joy in their practice, achieve skill mastery, and foster the development of physical, mental, and aesthetic qualities, alongside virtues and etiquette. Additionally, building a supportive CMAs community and cultivating a sense of ritual are essential. Such strategies are intended to reinforce practitioners’ self-affirmation and group identity, thus boosting their Sense of Belonging and encouraging their continued engagement in CMAs.